Listenership of Farmers' Digest Radio Program on Joy FM (96.5), Otukpo, Benue State, Nigeria. Issue 1 (2nd January 2017) - Badiru, Idris Olabode; Ladigbolu, Temitope Adejoju; Bodaga, Thaddeus
ABSTRACT: The study investigated listenership of the Farmers' Digest radio program on Joy FM (96.5) in Otukpo, Benue State, Nigeria. A questionnaire was used to collect data on listenership of Farmers' Digest, preferred segment, listeners' perception, and factors limiting listenership of the program from 150 respondents. Farmers' Digest enjoyed wide listenership (56.3%) and a favorable perception (74.4%). Discussion ( M = 1.79) was the most preferred segment and irregular supply of electricity ( M = 1.64) was the most limiting listenership factor. Perception was significantly related to program listenership ( r = .484). The program design should be sustained, while identified constraining factors should be mitigated for enhanced listenership.